Levinas on Death - An interpretation of Edvard Munch’s The Death of Marat II (1907) - Jonas M. N. Sörensen (Nordicum-Mediterraneum, 2013)
Due to Levinas we experience the death of the Other as the end of the Others capacity of expression. By interpreting Edvard Munch’s painting The Death of Marat that unlike David’s canonical painting of Marat is portraying both Marat and his killer Corday, I want to put Levinas’ thesis stating our responsibility for the Other as infinite into play. Care constitutes a fundamental brick in Levinas’ grand plan - to make ethics a first philosophy. In his thinking on death Levinas elaborate on a concept of durability that I will look into, as well as his use of the words darkness and light in describing our relation to death. In his thinking of the death of the Other Levinas refers to Kierkegaard and Sartre and to Heidegger’s thinking on time.